2018
DOI: 10.1177/0009922818787868
|View full text |Cite
|
Sign up to set email alerts
|

Outreach and Reminders to Improve Human Papillomavirus Vaccination in an Integrated Primary Care System

Abstract: This study evaluated the impact of health system-based outreach and reminders on human papillomavirus (HPV) vaccine series initiation and completion. Parents of 10 to 12 year olds (n = 1805) were randomized to receive either (1) an outreach letter and brochure recommending HPV vaccination followed by automated HPV vaccine reminders or (2) usual care. We interviewed a subset of 50 parents to assess program acceptability. Outcomes were HPV vaccine initiation during the study period and on-time series completion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(66 citation statements)
references
References 28 publications
0
66
0
Order By: Relevance
“…Reported HPV vaccine series completion rates also varied between studies (Table 5). Generally, series completion rates improved in the intervention group compared with the control group (Cates et al, 2018; Henrikson et al, 2018; McGaffey et al; Perkins et al, 2020; Zimmerman et al, 2017). Studies by McClean et al (2017) and Szilagyi et al (2015, 2020) did not demonstrate any improvement with the interventions implemented.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Reported HPV vaccine series completion rates also varied between studies (Table 5). Generally, series completion rates improved in the intervention group compared with the control group (Cates et al, 2018; Henrikson et al, 2018; McGaffey et al; Perkins et al, 2020; Zimmerman et al, 2017). Studies by McClean et al (2017) and Szilagyi et al (2015, 2020) did not demonstrate any improvement with the interventions implemented.…”
Section: Resultsmentioning
confidence: 99%
“…Reported HPV vaccine series initiation rates varied between studies (Tables 4 and 5). Overall, vaccine series initiation rates improved in the intervention group compared with the control group (Bar‐Shain et al, 2015; Henrikson et al, 2018; McGaffey et al, 2018; Perkins et al, 2020; Rand et al, 2017; Zimmerman et al, 2017) ; however, McClean et al (2017) noted that children in the age group of 13–17 years were not significantly influenced by the intervention, while children in the age group of 11–12 years were significantly influenced. Szilagyi et al (2020) only reported improvement in initiation rates following a single phone call in Colorado practices, but otherwise did not report any improvements following intervention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations